EVALUASI PENYELENGGARAAN PEMILU TERKAIT REGULASI PENCORETAN/PEMBENARAN HASIL PENGHITUNGAN SUARA - Wilma Silalahi (Jurnal Bawaslu Provinsi Kepulauan Riau, 2025)
The implementation of the 2024 simultaneous general elections has left a number of challenges for election management bodies. Various issues and disputes that arose during the electoral process serve as important notes for future election administration. However, problems and disputes are inseparable from the conduct of elections, thereby necessitating a comprehensive evaluation of election implementation. Therefore, the main issue examined in this study is the evaluation of election administration related to the regulation on the correction or amendment of vote-counting results. This paper does not aim to suggest that the administration of the 2024 elections was ineffective or suboptimal; rather, it seeks to examine another perspective on whether existing electoral regulations have adequately accommodated and provided legal certainty for all citizens of Indonesia, considering that elections constitute the largest democratic event conducted by the Indonesian nation. This study employs normative juridical legal research, which holds that the formation of laws and regulations must comply with the mandates of Pancasila and the 1945 Constitution of the Republic of Indonesia as the highest legal authority within the Indonesian legal system, or what Wignjosoebroto refers to as doctrinal legal research. In the event of corrections or amendments to copy forms, such corrections are made by striking through numbers or words with two horizontal lines and writing the corrected numbers or words above the crossed-out text, accompanied by the initials of the Chairperson of the Polling Station Working Committee (KPPS) and the witnesses present. Meanwhile, corrections to the Model C.Hasil Plano form are carried out using correction fluid (tipp-ex) without initials, as the form will be photographed and subsequently uploaded to the Sirekap system. The evaluation of election administration, particularly regarding the correction or amendment of vote-counting results, requires broader dissemination and socialization of the relevant regulations. Furthermore, electoral regulations must be aligned with developments in the constitutional system and the needs of Indonesian society and the nation.